Direitos e financiamento do sistema de saúde: repasses e aplicação de recursos em ações e serviços de saúde no município de São Luís - MA - QUEIROZ, Fernanda Dayane dos Santos (2018)
When talking about the right to health in Brazil, there is no doubt that the great landmark was the Federal Constitution of 1988, which states that health is the right of everyone and the duty of the State. However, the State has difficulties in achieving the realization of the right to health, since there are problems involving the distribution of competences - with a view to the configuration of our cooperative federalism - and the finiteness of resources - making it difficult to guarantee the universality of the law. This research intends to evaluate the configuration of sanitary federalism based on the distribution of resources directed to the municipality of Sao Luis-MA, constituted and legally foreseen, in the period from 2012 to 2016. Therefore, it is necessary to evaluate the public health financing in the city of Sao Luis, which was constitutionally considered a federative endowed with autonomy. Based on this research, it is sought to understand the federal federative design and the distribution of resources directed to health care in order to characterize or not the municipality as a de facto federated entity. It is a research of documentary, bibliographical, exploratory analysis that uses, as a methodological framework, Max Weber and as a theoretical framework, the use of John Rawls's theory of Justice by Norman Daniels, in which one intends to identify to what extent one can speak in federalism of health since the economies of the municipalities of the country - more specifically, of Sao Luis - are maintained by transfers of health resources coming from the Union.